Promising Practices Used By EFL Teachers in Teaching aand Learning Process - Rezky Uspayanti (Universitas Musamus, 2019)
This study focused on promising practices used by EFL teachers in teaching and learning process. This study applied descriptive qualitative which focused on discourse analysis. This qualitative study involved non-numeric data. This study was conducted in Junior High School 2 Pinrang that focused on 18 students in VIII.4 and 18 students in VIII.5 and two English teachers as the participants. The instruments were recording namely video camera and sound recording to record the teachers’ promising practices, interview the teachers to clarify the promising practices used and to ask about the implication of promising practice in teaching and learning process. Thus, interview the students to know their responses on promising practices used by teacher. Based on the result, the teacher A and B mostly used commisisve speech act that function as promising in teaching and learning process. Promising utterance is making the students prepare their self in learning process. The result of obeservation and interview from the teachers, the commisisve speech act as promising not only has function to promise but also to assert, so the students can prepare their self and doing their homework. The students also gave positive responses on promising practices used by EFL teachers. Thus, it also gave implication in TEFL.